2011
DOI: 10.1139/y11-012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of metabolic and cardiac dysfunctions by insulin sensitizers and angiotensin receptor blocker in rat model of type 2 diabetes mellitus

Abstract: The objective of this study was to investigate the modulation of metabolic dysfunctions, adiponectin levels, and cardiac dysfunctions of type 2 diabetes mellitus (T2DM) by a combination of the insulin sensitizer rosiglitazone and angiotensin receptor blocker telmisartan in an experimental rat model. Fifty male adult Sprague-Dawley rats were divided equally into 5 groups. Group I: fed normal chow; served as normal control group. Groups II-V: fed a high-fat diet (HFD) for 2 weeks, followed by injection of strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The present study found high blood glucose with relative insulin deficiency and high HOMA-IR in the DM group, indicating T2DM development. Previous studies reported similar findings [18,22,23]. Lack of insulin and hyperglycemia developed in this animal model could be due to partial damage of pancreatic β-cells via the cytotoxic action of STZ and block of insulin receptors by a high-fat diet [22,23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study found high blood glucose with relative insulin deficiency and high HOMA-IR in the DM group, indicating T2DM development. Previous studies reported similar findings [18,22,23]. Lack of insulin and hyperglycemia developed in this animal model could be due to partial damage of pancreatic β-cells via the cytotoxic action of STZ and block of insulin receptors by a high-fat diet [22,23].…”
Section: Discussionsupporting
confidence: 77%
“…The details of induction of Type 2 DM in rats was mentioned in our previous study [18]. Briefly, rats were given a high-fat diet for 4 weeks.…”
Section: Type 2 Dm Rat Modelmentioning
confidence: 99%
“…Therefore, PPAR-γ agonists used in our study probably in uenced the gene expression responsible for lipid and carbohydrate metabolism without affecting glycaemic levels in diabetic SHRs. To support our observations previous observation proved that pioglitazone attenuated dyslipidemia in cyclosporine induced hypertensive rats (65), whereas, in another study, Hussain proved a much greater bene cial effect of a combination of rosiglitazone and telmisartan offered more improvement in serum TGs and adiponectin (66). Interestingly, treating diabetic rats with exogenous adiponectin and pioglitazone as full PPAR-γ agonist, produced signi cant attenuation of metabolic dysfunctions, as evidenced by the signi cant decrease in TC, TGs, LDL, but an increase in HDL and adiponectin plasma concentrations as similar conclusion were drawn for plasma adiponectin concentration.…”
Section: Adiponectin Concentration In Plasma and Lipid Pro Lesupporting
confidence: 86%
“…previous study done by [21] we can make a model of type 2 diabetes as each rat received high fat diet for 4 weeks then streptozotocin (STZ) (35 mg/Kg) was injected intraperitoneally. These rats were considered diabetic when rats tail blood sugar > 200 mg/dL after 48 h after injection.…”
Section: Group 2 (Dm Positive Control): Accordingmentioning
confidence: 99%